Collaborative Strategy in Tertiary Prevention of Drug Abuse: Active Role of Community and Government Institutions in Rehabilitation and Reintegration of Drug Victims - Pangeran Baron; Puspitasari Puspitasari; Stanislaus Riyanta (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
This article discusses collaborative strategies in tertiary prevention of drug abuse, with a focus on the active role of the community and government institutions in the rehabilitation and reintegration of drug victims. Through the literature review method, this article explores various efforts involving various parties in dealing with drugs. The research results show that the dynamics of the process in dealing with drugs are good, including the promotion of shared principles, shared motivation and the capacity to take action. Collaborative actions have also been good, including facilitating and advancing the collaboration process. The impact and adaptation of collaboration in dealing with drugs has also been good, trying to suppress drug users. Overall, efforts to rehabilitate and reintegrate drug users into society are complex efforts and require cooperation from various parties. Support is needed from the government, non-governmental organizations, family, friends and society as a whole to facilitate the rehabilitation and reintegration process of drug users into society. With effective rehabilitation and reintegration efforts, drug users can be expected to return to living normal and productive lives in society. Apart from that, rehabilitation and reintegration efforts can also help reduce the rate of drug abuse and improve the quality of life of society as a whole.